1967
DOI: 10.1172/jci105551
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Movement in the Small Intestine: Preferential Transport by the Ileum *

Abstract: Summary. Isolated, surviving sacs of everted small intestine were used to characterize ammonia transport in the golden hamster. Jejunal and ileal sacs incubated aerobically in ammonia-free test solution liberated the same quantity of ammonia as did sacs that were filled and immediately emptied of their contents, indicating no significant evolution of metabolic ammonia.Under aerobic conditions, ileal sacs transferred a solution of high ammonia content from the mucosal surface to the serosal surface against a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

1975
1975
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…Small intestinal ammonia transport may be mediated, at least in part, by the NH 4 ϩ /H ϩ exchange activity present in small intestinal brush-border vesicles that has a K m for ammonia of ϳ1 mM (32). This apical NH 4 ϩ /H ϩ exchange activity is consistent with the observation that increasing luminal H ϩ concentration increases small intestinal ammonia secretion (34,35,45,46). RhCG is a candidate protein to mediate this apical NH 4 ϩ /H ϩ exchange activity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Small intestinal ammonia transport may be mediated, at least in part, by the NH 4 ϩ /H ϩ exchange activity present in small intestinal brush-border vesicles that has a K m for ammonia of ϳ1 mM (32). This apical NH 4 ϩ /H ϩ exchange activity is consistent with the observation that increasing luminal H ϩ concentration increases small intestinal ammonia secretion (34,35,45,46). RhCG is a candidate protein to mediate this apical NH 4 ϩ /H ϩ exchange activity.…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, small intestinal ammonia transport is energy-dependent, saturable, and exhibits Michaelis-Menton constant kinetics (34,35), and recalculation of published data suggest that the K m for luminal ammonia absorption is ϳ7 mM (35). Small intestinal ammonia transport may be mediated, at least in part, by the NH 4 ϩ /H ϩ exchange activity present in small intestinal brush-border vesicles that has a K m for ammonia of ϳ1 mM (32).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of ammonia absorption by the colon is not fully understood. Distal ileum is thought to possess transport pathways for the active absorption of NH' (35). Cohen et al, however, observed that in rat distal colon, NH3 is 400 times more permeant than NH', and suggested that passive absorption of NH3 may be quantitatively more important than transport of NH' at physiological fecal pH (33).…”
Section: Discussionmentioning
confidence: 99%
“…III.B.). Moreover, some further criteria of active transport [126,268,[299][300][301][302]304,331] are concerned with its dependence on the intensity of cell metabolism [29,112,121,125,144,228,238,259,284], inhibition of it by a fall in temperature [261], and metabolic poisons [29,209,238], by O 2 , and substrate deficiency. The accumulation of a permeant in the cell interior, as proposed by LING [187], TROSHIN [295], HARRIS and PRANKERD [106], SHAW et aI.…”
Section: Active Transportmentioning
confidence: 99%